Alarming nutrient pollution of Chinese rivers as a result of agricultural transitions - Maryna Strokal; Lin Ma; Zhaohai Bai; Shengji Luan; Carolien Kroeze; Oene Oenema; Gerard Velthof; Fusuo Zhang (Environmental Research Letters, 2016)
Transitions in Chinese agriculture resulted in industrial animal production systems, disconnected from crop production. We analyzed side-effects of these transitions on total dissolved nitrogen (TDN) and phosphorus (TDP) inputs to rivers. In 2000, when transitions were ongoing, 30%–70% of the manure was directly discharged to rivers (range for sub-basins). Before the transition (1970) this was only 5%. Meanwhile, animal numbers more than doubled. As a result, TDN and TDP inputs to rivers increased 2- to 45-fold (range for sub-basins) during 1970–2000. Direct manure discharge accounts for over two-thirds of nutrients in the northern rivers and for 20%–95% of nutrients in the central and southern rivers. Environmental concern is growing in China. However, in the future, direct manure inputs may increase. Animal production is the largest cause of aquatic eutrophication. Our study is a warning signal and an urgent call for action to recycle animal manure in arable farming.